Student satisfaction and learning needs in distant education: Towards lecturers’ pedagogical strategies and attitude - Syed Hassan, Sharifah Sariah; Abdul Hamid, Siti Rafiah; Ustati, Rusmanizah (Mediterranean Center of Social and Educational Research Publishing, Rome-Italy, 2013)
Blended learning involves both traditional face to face classroom teaching and e-learning approach. To date, past research in Malaysia focused much on the effectiveness and acceptace of e-learning (Ndubisi, 2006); attitude towards e-MBA (Mahmod, Dahlan, Ramayah, Karia, Asaari, Muhammad & Abu Hassan, 2005) as well as factors affecting students’ willingness and commitment to use e-learning continuously (Ramayah, et. al.; 2010). However, the system can only be accepted by students when there are effective teaching strategies. Further, learning structure must be well-structured to enable students to persist and maintain their engagement in the e-learning environment. The present study has investigated student learning via the use of e-learning and face to face approaches. The major focus of this study was to examine the students’ experiences and their level of satisfaction via quantitative and qualitative methods. Using self constructed questionnaire, the satisfaction of student learning is determined by the lecturer’s teaching strategies and lecturer’s attitude or awareness towards the whole concept of distant learning itself. The samples of the quantitative study involved 400 students majoring in English Language, Counselling and Islamic Education at one of the faculties in a Public University in Malaysia which was analysed using Multiple regression analyses. The qualitative study focused on interviews related to students’ satisfaction based on Michael Moore’s Theory of Transactional Distance related to lecturer and learning management system (LMS). Findings from this study indicated satisfaction in learning at the University via blended mode of distant learning approach. However, some of the emerging themes from the interviews have further highlighted the issues and challenges in distant education.